Concordance of links with identical Alexander invariants. (8th April 2014) - Cha, Jae Choon; Friedl, Stefan; Powell, Mark
Abstract : Davis showed that the topological concordance class of a link in the 3‐sphere is uniquely determined by its Alexander polynomial for 2‐component links with Alexander polynomial one. A similar result for knots with Alexander polynomial one was shown earlier by Freedman. We prove that these two cases are the only exceptional cases, by showing that the link concordance class is not determined by the Alexander invariants in any other case.